Climatic impact of activities : methodological guide for analysis and action - Rossignol, Jean-Yves (ISTE, Ltd. ; John Wiley & Sons, Inc., 2020)
Where the environment is concerned, regardless of scale, the logic of the Native American hummingbird which u0093does its partu0094 should prevail. To act independently of others is indeed the sine qua non of the global shift towards a regenerative economy of humanity and ecosystems, expurgating the pervading pollution (particularly from oil use). Small- and medium-sized enterprises, which this book especially targets, do not need disproportionately-sized study facilities in order to reduce their impact on global warming. Climatic Impact of Activities provides valuable methodological and practical support for establishing a complete and reliable diagnosis of the greenhouse effect, and for planning the corresponding corrective actions. This book guides the reader step by step in developing an informed emissions assessment with realistic and advanced case studies, in full compliance with official methodological recommendations.